STRATEGIES FOR CREATING HEADLINES ON SERBIAN ONLINE NEWS PORTALS - Kvapil, Milena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Online media are assuming greater role when it comes to informing public in Serbia, currently holding second place, after Television, which is still the main source of information. The article is based on empirical pilot research project which gave us basis for better understanding of how much the leading Serbian online media use the approach which can be described as „fake news“ or „clickbait“ strategy when it comes to creating News headlines, and how this can influence quality of their reporting. We have monitored all articles from „News“ section of three News portals in Serbia: Blic.rs, Kurir.rs and Telegraf.rs. Using the content analysis method, the headlines of the news were classified as „fake news“, „clickbait“ or „appropriate“. The additional research examined the headline as for their potential biased formulation, as well as usage of inappropriate wording. Research has shown that media in question are mostly using appropriate headlines, but there is also certain number of „fake news“ headlines, as well as a significant number of „clickbait“ headlines. It’s been noticed that these approaches were used for news that are most important for public information such as: politics, public health and general safety, what is a worrying tendency. The majority of biased headlines were related to political issues, which can imply undesirable lack of media objectivity. Inappropriate language (wording) has mostly been found in headlines covering Crime section, which can imply "tabloid" approach in those media.
Keywords: news, headlines, online, media, clickbait, fake news, reporting.